Топологічна еквівалентність функцій з класу F(D²) - Юрчук, І.А. (Інститут математики НАН України, 2006)
We construct the combinatorial invariant of functions from a F(D²) class. Necessary and sufficient condition for a topological equivalence of such functions is obtained in terms of their invariants.